Gestão democrática na escola pública alagoana: interfaces com o Plano de Desenvolvimento da Escola (PDE – Escola) - Brito, Maria Betânia Gomes da Silva (2012)
This research is embedded in the field of study of the planning and evaluation of educational management in the context of Brazilian public schools, from legal landmark built in the 1990s, after the promulgation of the Constitution of 1988, which was preceded by demands for a school participatory. To reach these considerations, three blocks were demarcated analysis: first, the concepts, meanings, history and implications of democratic management in school, twentieth century to century, then the reflection on the democratic management in public school and Alagoas its developments within the PDE-School, and finally, the third time, stands out the changes undertaken in the school under the logic of the PDE-School. Thus, the goal of understanding the meanings of democratic management in planning the Law of Guidelines and Bases of National Education no. º 9.394/96 and the design of the various groups present in this context, based on the preparation of the School Development Plan, after Decree 6. 094 of April 24, 2007. In this sense, the work addresses contemporary categories like state and its development in basic education policy, sent to public schools in the country. It was necessary in this historical and methodological analysis of the categories that were inferred from empirical data, such as: school, strategic planning, development, management and democratic participation. Thus, the analysis was built on the basis of selected sources in the design of work, through the reports of the subjects, the relationship of these lines with the organic theory elaborated by promoting the intersection of ideas and theoretical construct raised by the authors that sedimented research. The approach was configured as qualitative research ocuments and literature, with the theoretical and methodological discussions raised by the following authors: Bobbio (1987), Coutinho (1992, 2006); Frigotto (2003), Gramsci (2004, 2002, 1989) ; Höfling (2001); Neves (2005); Hochman, Arretche and Marques (2007); Hypólito (2008), Fonseca et al. (2004); Arelaro (2000), Azevedo (1997); Coraggio (2000), Golden (2007), Ferreira (2008), Haddad (2008), Oliveira (2009); Krawczyk (2000 and 2008), Motta (2008) ; Paulani (2006); Behring (2008); gruppi (1987); Harwey (1993); Mészáros (2002), among others. Noteworthy is the PDE-School as constitutive object of analysis, a central element of the discussion, allowing to identify the public policy of democratic management determinants of modern democracy, planning and participation, bringing contemporary school as a focus of study. The analysis points to a process of management by results, driven by the advance of neoliberal policies, leading to public school in the guidelines of international organizations that fund national education.